2014
DOI: 10.1159/000360583
|View full text |Cite
|
Sign up to set email alerts
|

Human Striatum Remodelling after Neurotransplantation in Huntington's Disease

Abstract: Background: Restoration of functions in Huntington's disease (HD) by neurotransplantation stems from the formation of a striatum-like structure capable of establishing host connections as a result of grafted striatal neuroblast maturation. For the first time, we demonstrated some developmental steps accomplished by progenitor cells in the brain of an HD patient and analysed the molecular asset of the human primordium. Case Report: Surgery involved bilateral (two sessions) stereotactic, caudate-putaminal transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Despite this, the safety and efficacy of transplanting hWGE tissue has been investigated in early phase clinical trials, in which HD patients received either cell suspension or diced tissue transplants. The results obtained from follow-up assessments administered up to 6 years postgraft have confirmed the safety of the procedure and the survival of metabolically active tissue transplants (14,15,20,4). Interestingly, in one safety study, three out of five grafted patients demonstrated long-term stabilization of performance on motor and cognitive tasks relative to a nongrafted cohort of patients who demonstrated a progressive deterioration of these functions.…”
Section: Introductionmentioning
confidence: 54%
“…Despite this, the safety and efficacy of transplanting hWGE tissue has been investigated in early phase clinical trials, in which HD patients received either cell suspension or diced tissue transplants. The results obtained from follow-up assessments administered up to 6 years postgraft have confirmed the safety of the procedure and the survival of metabolically active tissue transplants (14,15,20,4). Interestingly, in one safety study, three out of five grafted patients demonstrated long-term stabilization of performance on motor and cognitive tasks relative to a nongrafted cohort of patients who demonstrated a progressive deterioration of these functions.…”
Section: Introductionmentioning
confidence: 54%
“…Briefly, striatal tissue from 9 to 12 weeks old legally aborted human fetuses were obtained according to Italian National Institute of Health ethical guidelines. The use of human fetal tissue for research purposes was approved by the National Ethics Committee and the Committee for investigation in Humans of the University of Florence (Protocol n°678304) (Gallina et al, 2008(Gallina et al, , 2010(Gallina et al, , 2014. Striatal tissue was dissected from 3 human fetuses under sterile conditions, cut into fragments and enzymatically digested by 1 mg/ml collagenase type IV (Sigma-Aldrich Corp., St. Louis, MO, USA) incubation.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Preliminary evidence of functional efficacy in human transplants comes from a seminal French study that reported human fetal-derived graft survival and significant improvements in both motor and cognitive function in three patients over an approximately six-year period ( Bachoud-LĂŠvi et al., 2000 , Bachoud-LĂŠvi et al., 2006 ). Enhanced FDG-positron emission tomography signal in the frontal cortex of these individuals suggested that the implanted cells had integrated into the striatal neural circuitry and made functional connections with relevant cortical regions ( Gallina et al., 2014 ). The proof-of-concept provided by this study is encouraging and demonstrates that transplantation of “native” developing MSNs into the damaged striatum can produce functional improvements in at least some patients with HD.…”
Section: Introductionmentioning
confidence: 99%